Establishing a new water tariff method that complies with european principles and respects statutory autonomy: The case of South Tyrol. (June 2020) - Romano, Giulia; Guerrini, Andrea; Senoner, Thomas
Abstract: This paper describes a path-dependent regulatory process to define a new water-tariff calculation method for European regions and provinces requiring context-specific regulation. In 2017, South Tyrol, an autonomous province in north Italy, decided to design a new water tariff-setting method. The case of South Tyrol illustrates the application of the action research method. It offers insights on the regulatory tools available to define new water-tariff methods that comply with national and international frameworks, while considering contextual specificities that require simplicity (i.e., clarity and administrative ease). The results encourage using different regulatory instruments, following a contingency approach, to create diverse tariff structures. Highlights: The paper describes a path-dependent regulatory process in an autonomous province. It shows relevant tools to define new methods considering contextual specificities. The case of South Tyrol illustrates the application of the action research method.